2020
DOI: 10.3847/1538-4357/ab982b
|View full text |Cite
|
Sign up to set email alerts
|

The Multiwavelength Counterparts of Fast Radio Bursts

Abstract: The engines that produce extragalactic fast radio bursts (FRBs), and the mechanism by which the emission is generated, remain unknown. Many FRB models predict prompt multiwavelength counterparts, which can be used to refine our knowledge of these fundamentals of the FRB phenomenon. However, several previous targeted searches for prompt FRB counterparts have yielded no detections and have additionally not reached sufficient sensitivity with respect to the predictions. In this work, we demonstrate a technique to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 67 publications
(78 reference statements)
4
34
2
Order By: Relevance
“…Extending the same model to the shock properties derived for the observed populations of cosmological FRBs predicts that the afterglow emission for these more energetic bursts will occur at much higher energies,  E peak MeV-GeV, in the gamma-ray band (Figure 8). Unfortunately, gamma-ray satellites like Swift and Fermi are generally not sensitive enough to detect this emission to the cosmological distances of most FRB sources (Metzger et al 2019;Chen et al 2020;Margalit et al 2020). We furthermore emphasize that this predicted short (∼milliseconds duration) gamma-ray signal from the shocks is distinct from the longer-lasting and typically softer gamma-ray emission observed from giant Galactic magnetar flares (e.g., Hurley et al 2005;Palmer et al 2005), which is instead well explained as a pair fireball generated by dissipation very close to the NS surface.…”
Section: Baryonic Shellmentioning
confidence: 99%
See 1 more Smart Citation
“…Extending the same model to the shock properties derived for the observed populations of cosmological FRBs predicts that the afterglow emission for these more energetic bursts will occur at much higher energies,  E peak MeV-GeV, in the gamma-ray band (Figure 8). Unfortunately, gamma-ray satellites like Swift and Fermi are generally not sensitive enough to detect this emission to the cosmological distances of most FRB sources (Metzger et al 2019;Chen et al 2020;Margalit et al 2020). We furthermore emphasize that this predicted short (∼milliseconds duration) gamma-ray signal from the shocks is distinct from the longer-lasting and typically softer gamma-ray emission observed from giant Galactic magnetar flares (e.g., Hurley et al 2005;Palmer et al 2005), which is instead well explained as a pair fireball generated by dissipation very close to the NS surface.…”
Section: Baryonic Shellmentioning
confidence: 99%
“…In curvature models, the FRB is produced by curvature radiation from bunched electrons streaming along the magnetic field lines of the magnetar (e.g., Kumar et al 2017;Lu & Kumar 2018). These models predict fluence ratios h~1 in all bands (Chen et al 2020) and thus cannot explain the properties of the observed X-ray burst of SGR 1935+2154(whose fluence ratio is  h~-10 1…”
Section: Additional Modelsmentioning
confidence: 99%
“…Since the theoretical predictions for multiwavelength counterparts are not well constrained enough to interpret our upper limits directly, we only briefly compare them to our NIR observational data. Chen et al (2020) provide a summary of the predictions for the fluence in the aforementioned models. In the case of the relativistic shock interaction model by Beloborodov (2020), if the the blast wave strikes a wind bubble in the tail of a previous flare, a bright optical flare could result with an optical to radio fluence ratio of    10 opt radio 5 (Chen et al 2020).…”
Section: Comparison To Theoretical Modelsmentioning
confidence: 99%
“…Chen et al (2020) provide a summary of the predictions for the fluence in the aforementioned models. In the case of the relativistic shock interaction model by Beloborodov (2020), if the the blast wave strikes a wind bubble in the tail of a previous flare, a bright optical flare could result with an optical to radio fluence ratio of    10 opt radio 5 (Chen et al 2020). If some X-ray bursts from SGR 1935+2154 during the PGIR campaign were accompanied by a radio burst similar to FRB 200428, then we have the corresponding prediction of R NIR 0.1 for ).…”
Section: Comparison To Theoretical Modelsmentioning
confidence: 99%
“…The first decade of FRB searches was undertaken with telescopes that had localization regions ?1 arcmin 2 . This is inhibited by the seeming lack of "afterglows" analogous to those observed for GRBs (Petroff et al 2017;Bhandari et al 2018;Chen et al 2020) and associated supernova-like transient counterparts (Marnoch et al 2020). A precise localization (∼1″) of the burst itself is thus required to robustly identify the associated host galaxy (Eftekhari & Berger 2017).…”
Section: Introductionmentioning
confidence: 99%